2016
DOI: 10.1111/efp.12298
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a pine pathogen enhances growth and disease resistance inPinus radiataseedlings

Abstract: Most studies of Fusarium circinatum, the cause of pitch canker in pines, have focused on its activity as a pathogen. However, recent findings indicate that this fungus can colonize roots of Pinus radiata without inducing symptoms. Contrary to expectations, this study revealed that seedlings grown in infested sand grew more rapidly than seedlings not exposed to F. circinatum, based on root and shoot biomass, with modifications to root system architecture, including increased mycorrhizal root development.These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…For example, a known pine pathogen was found to cause growth enhancement and disease resistance in its host depending on the amount and duration of exposure (Swett & Gordon, ). Part of this pathogen's benefit could have resulted from increased mycorrhization of roots observed in the treated plants (Swett & Gordon, ), highlighting the importance of interactions between plant‐associated microbes in determining plant success. Previous studies show that certain bacterial or fungal endophytes can inhibit colonization and growth of plant pathogens (Arnold et al ., ; Tellenbach & Sieber, ; Adame‐Álvarez et al ., ; Hugentobler et al ., ; Terhonen et al ., ), so strong pathogenic effects of individual fungi in the laboratory might also be a result of release from the mediating effects of other microbiome members.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a known pine pathogen was found to cause growth enhancement and disease resistance in its host depending on the amount and duration of exposure (Swett & Gordon, ). Part of this pathogen's benefit could have resulted from increased mycorrhization of roots observed in the treated plants (Swett & Gordon, ), highlighting the importance of interactions between plant‐associated microbes in determining plant success. Previous studies show that certain bacterial or fungal endophytes can inhibit colonization and growth of plant pathogens (Arnold et al ., ; Tellenbach & Sieber, ; Adame‐Álvarez et al ., ; Hugentobler et al ., ; Terhonen et al ., ), so strong pathogenic effects of individual fungi in the laboratory might also be a result of release from the mediating effects of other microbiome members.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study support previous findings that F. circinatum is not solely a necrotrophic pathogen. This includes documentation that the pine pathogen can exist as a symptomless endophyte in the roots of a susceptible pine (Swett & Gordon, ; Swett et al., ) and that it can infect grasses without inducing symptoms (Swett & Gordon, ). This broader view of a host–pathogen relationship reinforces the perception that pure necrotrophy, in which nutrients are derived from cells killed by the pathogen during or in advance of colonization, is less common than previously thought (Van Kan, Shaw, & Grant‐Downton, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become apparent that this categorization oversimplifies the relationship between F. circinatum and its pine hosts. It is now well established that pine roots can sustain infections without visible damage (Swett & Gordon, 2017;Swett et al, 2016) and that root infections can occur in the absence of wounding (Martín-Rodrigues et al, 2015). Evidence that infections of shoot tissue do not require a wound was presented by Hepting and Roth (1946), who reported that seven of ten inoculations without wounding resulted in cankers.…”
Section: Discussionmentioning
confidence: 99%
“…This observation probably explains disease remission in long‐term monitoring plots (Gordon et al ., ), in which numerous trees that were initially severely diseased were free of symptoms and infections 3 years later. Similarly, exposure of stems and roots of P. radiata seedlings to F. circinatum enhanced resistance to shoot infections by the same fungus and promoted survival following subsequent stem inoculations (Bonello et al ., ; Gordon et al ., ; Swett & Gordon, ). Elevated host resistance occurred both when seedlings were grown in infested sand and when exposure to inoculum resulted from emergence through infested leaf litter (Swett & Gordon, ).…”
Section: Other Environmentally Friendly Approaches For Controlling Fmentioning
confidence: 99%